Manipulation of ascorbate biosynthesis in Solanum lycopersicum (cv Money maker) - Cronje, Christelle (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MSc (Plant Biotechnology))--University of Stellenbosch, 2010.